Music and crisis - Milenković Ivan (Muzikologija, 2016)
In this article the author does not consider crisis a threat, but in a modern sense, an auto-motive drive of art. Therefore, crisis does not affect the art from the outside, it does not hit it as an illness or a storm, but it always produces itself, which is considered to be a condition for movement in art. First of all, the author analyzes the notion of representation and the four roots of the sufficient reason as a conservative and conserving element of art, to which he opposes crisis and its self-production as something that resists sclerotization of art forms. In music, the relation between the ossified, "naturalized" structure and that which decomposes that structure, manifests itself as the relation between harmony and disharmony. The moment when harmony shows a tendency towards naturality, understanding eternity and truth, an alarm is activated to show that music is being paralyzed and it needs a deconstructive intervention of disharmony, atonality and dissonance.